2015
DOI: 10.1177/0022022115587026
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Relationship Quality and Physical Health Across Racial and Ethnic Groups

Abstract: The association between relationship quality and physical health is well established. We examined whether this association was similar across different races and ethnicities. Relationship quality and health were assessed in three national samples from the United States: the National Survey of American Life, the National Latino and Asian American Study, and the National Comorbidity Survey Replication (N = 9,020). Relationship quality was positively correlated with overall health across races and ethnicities; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…For example, Ma and Huebner (2008) note that parental relationships were stronger predictors of life satisfaction than peer relationships, with girls reporting higher levels of attachment to peers than boys. Overall, the quality of these peer relationships is particularly beneficial for psychological well-being (e.g., Tomé, de Matos, Camacho, Simões, & Diniz, 2014) and for improving health (McShall & Johnson, 2015). In fact, some research has suggested that for adolescents (Helsen, Vollebergh, & Meeus, 2000), peer relationship quality becomes more important than parental relationships (Furman & Buhrmester, 1992), with the benefits of peer relationships outweighing the effects of parental relationships (Hazan & Shaver, 1994) for health.…”
Section: Parent and Peer Relationshipsmentioning
confidence: 99%
“…For example, Ma and Huebner (2008) note that parental relationships were stronger predictors of life satisfaction than peer relationships, with girls reporting higher levels of attachment to peers than boys. Overall, the quality of these peer relationships is particularly beneficial for psychological well-being (e.g., Tomé, de Matos, Camacho, Simões, & Diniz, 2014) and for improving health (McShall & Johnson, 2015). In fact, some research has suggested that for adolescents (Helsen, Vollebergh, & Meeus, 2000), peer relationship quality becomes more important than parental relationships (Furman & Buhrmester, 1992), with the benefits of peer relationships outweighing the effects of parental relationships (Hazan & Shaver, 1994) for health.…”
Section: Parent and Peer Relationshipsmentioning
confidence: 99%
“…We tested an alternative hypothesis -that the mediating link is not specific to mothers' or fathers' insecurity of attachment, but rather to their general psychological distress (symptoms of anxiety and depression), aroused when conflict between them as a couple is unresolved. Evidence for this hypothesis derives from large national studies of the A-B connection showing that poor marital adjustment (high conflict, low satisfaction) is associated with depression and anxiety in men and women (McShall & Johnson, 2015;Whisman, Robustelli, & Labrecque, 2018). Completing the second leg of a mediation analysis B-C), studies show that parental depression and anxiety are consistently linked with parenting behavior that is harsh, intrusive, or distant (Lovejoy, Graczyk, O'Hare, & Neuman, 2000;Teetsel, Ginsburg, & Drake, 2014).…”
Section: An Alternative Mediation Hypothesismentioning
confidence: 99%
“…Accordingly, our null finding may imply that the relatively under-investigated cultural strength factors could be stronger predictors than SS, when three factors are investigated together in Latinos. It is also plausible that the function of SS may be better examined with more precise indicators containing more items (e.g., relationship quality, McShall & Johnson, 2015; or family bound, Ai, Aisenberg, et al, 2014; Ai, Pappas, et al, 2015; Sue & Sue, 2013) for Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that social connection and support in terms of one’s social capital can benefit individuals across racial and ethnic groups (McShall & Johnson, 2015). Relationship quality in social networks tends to be positively associated with the physical health of Latinos’ nationwide.…”
Section: Three Cultural Strengths and Latinos’ Srmh And Srhmentioning
confidence: 99%